Amplitude and phase fluctuations of an ultrasonic wave in a nonuniform medium - ŁABOWSKI, Miikołaj (Archives of Acoustics, 1980)
The paper presents the method of investigation of the results obtained for the fluctuation of quantities of the wave field in CO, close to the critical state. The method used the phenomenon of light diffraction by an ultrasonic wave. The analysis of the experimental results was performed by a correlation method, in which the autocorrelation functions and the power spectra of the fluctuation were determined for individual thermodynamic conditions and various frequencies of the ultrasonic wave.